Voltage stability analysis considering dynamic interaction for power systems integrated with multi-PMSGs - Cheng, Lin; Wang, Jili; Ke, Xianbo; Han, Zhiyong; Ai, Dongping (Frontiers in Energy Research, 2024)
This paper presents the dynamic voltage stability index based on voltage oscillation loop for power systems integrated with multiple permanent magnet synchronous generators (PMSGs) to assess the dynamic interaction on voltage stability. Firstly, the model of power systems integrated with multi-PMSGs using Q-V sensitivity matrix as feedback to connect all PMSGs are established. The transfer function model between voltage and reactive power is derived, and the voltage oscillation loop can be derived, which exists in each PMSG. Next, the dynamic voltage stability index is theoretically derived and given, the impact of dynamic interaction among multi-PMSGs on voltage stability can be quantified and the source of voltage oscillation can be identified and determined, then the voltage stability is recovered by shedding the trouble-making PMSG. The parameters of PMSGs could be tuned by the guidance of dynamic voltage stability index for reducing the risk of voltage oscillation. Finally, the example of test system with PMSGs is used to validate the correctness of the dynamic stability index. AC/DC microgrids. Reference [11] provides a new protection method of DC microgrids based on Fourier transform. Reference [12] discusses a selection of control aspects that are important for negative sequence current injection of type 4 wind turbines. A new WT and VSC-HVDC control method is proposed in [13], which can determine the reference voltage directly.Meanwhile, the voltage stability gains more and more attention due to high penetration of wind generation, the scholars have studied some strategies to improve voltage stability [14]- [18]. Reference [14] and [15] all improve voltage stability through the coordination of reactive power. The method of coordinated dynamic VAR source placement is applied for voltage stability enhancement in [16]-[17]. Voltage stability and control of offshore wind farms with AC collection and HVDC transmission is investigated through impedance models in [18]. The voltage stability is more complex with the dynamic interaction among the dynamic units, such as synchronous generators and wind generators [19]. Hence, proposing the voltage stability index to evaluate dynamic interaction quantitatively is necessary.